2020
DOI: 10.3390/antiox9080671
|View full text |Cite
|
Sign up to set email alerts
|

BVR-A Deficiency Leads to Autophagy Impairment through the Dysregulation of AMPK/mTOR Axis in the Brain—Implications for Neurodegeneration

Abstract: Biliverdin reductase-A (BVR-A) impairment is associated with increased accumulation of oxidatively-damaged proteins along with the impairment of autophagy in the brain during neurodegenerative disorders. Reduced autophagy inhibits the clearance of misfolded proteins, which then form neurotoxic aggregates promoting neuronal death. The aim of our study was to clarify the role for BVR-A in the regulation of the mTOR/autophagy axis by evaluating age-associated changes (2, 6 and 11 months) in cerebral cortex sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 83 publications
2
11
0
Order By: Relevance
“…Integrins interface with redox signaling by triggering oxidation and inhibition of phosphatases that dephosphorylate and inactivate FAK ( 82 ). In addition, loss of BVR in the cortex leads to the accumulation of oxidatively damaged proteins with impaired autophagy ( 83 ). As a result, both BVR and FAK are tightly linked to redox signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins interface with redox signaling by triggering oxidation and inhibition of phosphatases that dephosphorylate and inactivate FAK ( 82 ). In addition, loss of BVR in the cortex leads to the accumulation of oxidatively damaged proteins with impaired autophagy ( 83 ). As a result, both BVR and FAK are tightly linked to redox signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Beclin-1 is an important autophagy mediator, which increases autophagy ( 40 ). Furthermore, it has been reported that ATG7 promotes autophagy ( 41 ), while p62 is negatively associated with the autophagy process ( 42 ). The results of the current study were consistent with the aforementioned findings, suggesting that knockdown of FAM225B could inhibit the progression of HS by inhibiting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, both BVR and FAK are tightly linked to redox signaling. Additionally, loss of BVR in the cortex leads to the accumulation of oxidatively-damaged proteins with impaired autophagy ( 81 ). Interestingly, shRNA-mediated knockdown of BVR has been shown to impair LTP at CA3-CA1 synapses in hippocampal slices ( 82 ).…”
Section: Discussionmentioning
confidence: 99%